- Not to be confused with ε function or Nihilustheabsolutists E function.
Hyper-E notation | |
---|---|
Based on | Exponentiation |
Growth rate | \(f_{\omega}(n)\) |
Hyper-E Notation (E# for short) is a notation for large numbers devised by Sbiis Saibian.[1] It was first introduced on his Web book One to Infinity: A Finite Journey on November 19, 2011, and was generalized to Extended Hyper-E Notation (xE# for short). Hyper-E Notation is a refined version of a notation Sbiis Saibian devised as a child.
E# is not primitive recursive, and specifically the function E(n) = En##n eventually dominates all primitive recursive functions.[2] In fact, in the fast-growing hierarchy, \(n \mapsto\textrm E100\#\#n\) dominates \(f_n\) for all \(n < \omega\) and is itself dominated by \(f_\omega\).
E# and xE# form part of a larger notation, the Extensible-E System, that also encompasses Cascading-E Notation.
Nathan Ho and Wojowu proved termination for the rules of Hyper-E Notation.[3]
Original definition[]
The original Hyper-E Notation consists of a sequence an of one or more positive integer arguments separated by hyperions (or hyper marks) #. We notate this as E[b]a1#a2#...#an. b is called the base — if it is omitted, as it often is, it defaults to 10. "E[b]d" is also equal to "b^d".
The three rules are as follows:
- Rule 1. If there are no hyperions:
- \(\textrm E[b]x = b^x\).
- Rule 2. If the last entry is 1:
- \(\textrm E[b]{a_1}\#{a_2}\#{a_3}\cdots\#{a_n}\#1 = E[b]{a_1}\#{a_2}\#{a_3}\cdots\#{a_n}\).
- Rule 3. Otherwise(iteration last):
- \(\textrm E[b]{a_1}\#{a_2}\#{a_3}\cdots\#{a_{n-2}}\#{a_{n-1}}\#{a_n} =\)
- \(= \textrm E[b]{a_1}\#{a_2}\#{a_3}\cdots\#{a_{n-2}}\#(\textrm E[b]{a_1}\#{a_2}\#{a_3}\cdots\#{a_{n-2}}\#{a_{n-1}}\#{(a_n-1)})\)
In plain English:
- If there is only one argument x, the value of the expression is bx.
- If the last entry is 1, it may be removed.
- Otherwise...
- Evaluate the original expression, but with the last entry decreased by 1. Call this value z.
- Remove the last two entries of the expression.
- Add z as an entry to the end of the expression.
The priority of the rules are stated in the original webpage below the definition, "There are 3 rules used. If your given a E# expression, you first check to see if rule 1 applies. If it does not you check for rule 2. If that doesn't apply you go to 3." It disables \( a_n \) being 1 in the 3rd rule and avoids an overlapping case classification.
Extended definition[]
Extended Hyper-E notation | |
---|---|
Based on | hyperion marks |
Growth rate | \(f_{\omega^{\omega}}(n)\) |
Extended Hyper-E Notation allows multiple hyperions to appear between each entry. The number of hyperions following entry an is represented by h(n). For the sake of this definition, #n is a shorthand for n successive hyperion marks. For example, a full expression would be written E(b)a1#h(1)a2#h(2)...#h(n - 1)an#h(n). Saibian uses @ to indicate the rest of the expression such as Bowers uses # to indicate the rest of the array.
The difference between original and extended notation is that extended Hyper-E notation allows more than one consecutive #'s.
- Rule 1. If there are no hyperions:
- \(E(b)x = b^x\).
- Rule 2. If the last entry is 1:
- \(E(b) @ \#^{h(n-1)}{a_n}\#^{h(n)}1 = E(b) @ \#^{h(n-1)}{a_n}\).
- Rule 3. If \(h(n-1)>1\):
- \(E(b) @ \#^{h(n-2)}{a_{n-1}}\#^{h(n-1)}{a_n} = E(b) @ \#^{h(n-2)}{a_{n-1}}\#^{h(n-1)-1}{a_{n-1}}\#^{h(n-1)}{a_n-1}\).
- Rule 4. Otherwise:
- \(E(b) @ \#^{h(n-2)}{a_{n-1}}\#{a_n} = E(b) @ \#^{h(n-2)}(E(b) @ \#^{h(n-2)}{a_{n-1}}\#{a_n-1})\) (note \(\#^1\) = \(\#\)).
It seems similar to linear array notation rules. We can also rewrite it in plain English:
- If there is only one argument x, the value of the expression is bx.
- If the last entry is 1, it may be removed.
- Let h be the length of the last set of hyperion marks. If h > 1:
- Remove the last entry of the expression and call it r.
- Again remove the last entry of the expression; this time call it z.
- Repeat "z" r times with h - 1 hyperion marks in between each repetition. Append this to the end of the expression. (Restore a removed hyperion mark sequence to glue the two expressions together.)
- If the last set of hyperion marks is of length one:
- Evaluate the original expression, but with the last entry decreased by 1. Call this value z.
- Remove the last two entries of the expression.
- Add z as an entry to the end of the expression. (Again, restore a removed hyperion mark sequence to glue the two expressions together.)
Examples[]
- E6 = E6#1 = 106 = million
- E100 = E100#1 = 10100 = googol
- This is an example of rule 1 with a one-entry expressions. Since the base defaults to 10, we can abbreviate E(10)100 as E100.
- E100#2 = E(E100#1) = E10100 = 1010100 = googolplex
- E100#3 = E(E100#2) = E1010100 = 101010100 = googolduplex
- This is an example of rule 3 (rule 4 in the expansion) with a two-entry expressions. In the second expression, the parentheses can be omitted: E(E100#1) = EE100#1.
- E303#1 = E303 = eceton = centillion = 10303
- E303#2 = ecetonplex = EE303 = 1010303
- E303#3 = EEE303 = 101010303 = ecetonduplex
- E1#3 = EEE1 = 101010 = trialogue
- E1#4 = EEEE1 = 10101010 = tetralogue
- E1#10 = EEEEEEEEEE1 = 10^^10 = Decker
- E303#6 = EEEEEE303 = 101010101010303 = ecetonquintiplex
- E1#100 = EEE...EEE1 (100 E's) = giggol
- Repeated application of rule 3: E1#100 = EE1#99 = EEE1#98 = ...
- E100#100 = EEE...EEE100 (100 E's) = grangol
- This is the same as E1#100, but with a different first entry.
- E100#101 = EEE...EEE100 (101 E's) = grangolplex
- E100#101 = EE100#100 = 10grangol, hence the name.
- E100#100#2 = E100#(E100#100) = EEE...EEE100 (grangol E's) = grangoldex
- Now we enter three-entry expressions.
- E100#100#3 = E100#(E100#100#2) = E100#(E100#(E100#100)) = EEE...EEE100 (grangoldex E's) = grangoldudex
- Increasing the value of the third entry makes nesting deeper and deeper.
- E100#100#100#100 = E100#100#(E100#100#100#99) = E100#100#(E100#100#(E100#100#100#98)) = ... gigangol
- Four-entry expressions are similar — they create deeper and deeper nesting in the array level below them. This can also be written as E100##4; the beginning of the next level of the notation.
- E100##100 = E100#100#100#...#100#100#100 with 100 repetitions of 100 = gugold
- Now we have arrived at Extended Hyper-E Notation. Two successive hyperion marks (deutero-hyperions) indicate repetition at the lower level.
- E100##100#100 = graatagold
- This expression decomposes into Ea##b expressions by applying rule 4 repeatedly.
- E100##100##100 = E100##100#100#...#100#100 with 100 repetitions of 100 = gugolthra
- We ignore the first ## until the second one has been expanded and all the 100s have been solved.
- E100###100 = E100##100##...##100##100 with 100 repetitions of 100 = throogol
- Three hyperion marks (trito-hyperions) constitute a repetition of two hyperion marks. Remember, the double marks are solved from right to left.
- E100####100 = E100###100###...###100###100 with 100 repetitions of 100 = teroogol
- Quadruple hyperions decompose into triples.
- Godgahlah = E100#####...#####100 with 100 hyperion marks or E100#100100
- Sets of 100 hyperion marks decompose into 99s, 99s decompose into 98s, etc. Also note that the superscript 100 means that there are 100 #'s, and should not be confused with E100#(100100).
Relationship to Other Notations[]
The first segments of Hyper-E notation are based on exponentiation, i.e. En equals 10n. Nesting in a single-entry Hyper-E produces iterated exponentiation, such as EEEn=101010n. Then, hyperion marks come into play. Because hyperion marks are crucial to the recursion in this notation, certain arrangements of hyperions can indicate similarity to other notations defined by recursion.
Hyper-E can relate to arrow notation through the following rule: [4]
- \(a \uparrow^{c}b = E(a)\underbrace{1\#1\#...1\#}_{(1\#) \times (c-1)}b\)
for positive integers a, b, c. For example,
- a↑b = E(a)b
- a↑↑b = E(a)1#b
- a↑↑↑b = E(a)1#1#b
- a↑↑↑↑b = E(a)1#1#1#b
Pseudocode[]
For a fixed number of variables, the original Hyper-E Notation is primitive-recursive, although the values it produces are well beyond that of any computer. The extended Hyper-E Notation is nonprimitive-recursive for two variables or more.
function Eb(a1, a2, ..., an - 1, an): //Default value of b is 10 if n = 1: return ba1 if an = 1: return Eb(a1, a2, ..., an - 1) z := Eb(a1, a2, ..., an - 1, an - 1) return Eb(a1, a2, ..., an - 2, z) function xEb(a1, a2, ..., an - 1, an; h1, h2, ..., hn - 2, hn - 1): //Default value of b is 10 if n = 1: return ba1 if an = 1: return xEb(a1, a2, ..., an - 1; h1, h2, ..., hn - 2) if hn - 1 > 1: r := an z := an - 1 zseq := z, z, ..., z, z (r times) h := ah - 1 hseq := h, h, ..., h, h (r - 1 times) return xEb(a1, a2, ..., an - 2, zseq; h1, h2, ..., hn - 2, hseq) z := xEb(a1, a2, ..., an - 1; h1, h2, ..., hn - 2, hn - 1) return xEb(a1, a2, ..., an - 2, z; h1, h2, ..., hn - 2)